2008
DOI: 10.1140/epjb/e2008-00231-9
|View full text |Cite
|
Sign up to set email alerts
|

Microwave surface resistance of pristine and neutron-irradiated MgB2 samples in magnetic field

Abstract: Abstract. We report on the microwave surface resistance of two polycrystalline Mg 11 B2 samples; one consists of pristine material, the other has been irradiated at very high neutron fluence. It has already been reported that in the strongly irradiated sample the two gaps merge into a single value. The mw surface resistance has been measured in the linear regime as a function of the temperature and the DC magnetic field, at increasing and decreasing fields. The results obtained in the strongly irradiated sampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 51 publications
(189 reference statements)
5
23
0
Order By: Relevance
“…These results have been reported and discussed in Ref. [18]. In order to fit the data, we have determined the B profile inside the sample due to the critical state and calculated a proper averaged value of R s (B) over the whole sample.…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…These results have been reported and discussed in Ref. [18]. In order to fit the data, we have determined the B profile inside the sample due to the critical state and calculated a proper averaged value of R s (B) over the whole sample.…”
Section: Resultsmentioning
confidence: 55%
“…The lines are the best-fit curves obtained, as explained in Ref. [18], with µ 0 H c2 = 1.71 T, ω 0 /ω = 0.67 and the field dependence of the critical current density reported in Ref. [25].…”
Section: Experimental Apparatus and Samplementioning
confidence: 79%
See 2 more Smart Citations
“…It has already been shown that the in-field microwave (mw) response of two-gap MgB 2 superconductor cannot be accounted for by standard models for fluxon dynamics [1][2][3]. The anomalies have been ascribed to the unusual structure of fluxons, related to the different field dependence of the two superconducting gaps [4,5].…”
Section: Introductionmentioning
confidence: 99%